Toward Programmable Moiré Computation: Toward Programmable Moiré Computation (Adv. Theory Simul. 7/2021). Issue 7 (14th July 2021) - Gao, Yuechen; Ye, Shuqian; Lin, Haoxiang; Zhu, Xi
Abstract : A consecutive training process of Moiré computation framework from classification to sampling tasks is shown. In article number 2100063, Xi Zhu and co‐workers demonstrate that the optical properties of Moiré pattern are related to the twist angle, which can be controlled by advanced laser techniques. Rich choices of 2D materials as well as the programmable, non‐replacing features imply a promising development potential for Moiré computation.